Concanavalin A Induces Patching/Capping of the Platelet Membrane Glycoprotein llb/llla Complex - Kakaiya, R M; Kiraly, T L; Cable, R G (Thrombosis and Haemostasis, 1988)
Two recent reports have shown platelet patching/capping by concanavalin A (Con A). In these studies, Con A receptors were shown to mobilize from pseudopodia and lamellipodia to the central cell parts during platelet attachment and spreading. The molecular mechanism underlying Con A receptor capping was not examined in either study.Con a binds maximally to human platelet membrane glycoproteins IIb and IIIa. In order to test whether Con A-induced capping caused the capping of this membrane glycoprotein complex, we treated normal human platelets with unlabeled Con A. After fixation, platelets were further treated with mouse monoclonal antibodies against the membrane glycoprotein IIb/IIIa complex and stained with fluorescein isothiocyanate (FITC) tagged anti-mouse IgG. An average of 16% platelets manifested capping with one monoclonal antibody preparation (N = 2) and 12% with a second preparation (N = 2).Control studies showed that only 18% of normal human fresh platelets exhibit capping with FITC-Con A (N = 17). If platelets were first incubated with unlabeled Con A, followed by staining with FITC-labeled anti-Con A antibody, an average of 15% platelets manifested caps (N = 17). Capping was inhibited by methyl-alpha-D-mannopyranoside (a known inhibitor of Con A), at cold temperature and by pre-treatment of platelets with colchicine.Our studies confirm the earlier findings on Con A induced capping. Also, our findings suggest that the molecular mechanism for Con A receptor capping involves patching and capping of the platelet membrane glycoprotein IIb/IIIa complex. It is possible that glycoprotein Ilb/IIIa redistribution might be intimately involved during platelet attachment and spreading.
Keywords: Platelet capping; Concanavalin A; Platelet glycoproteins; Lectin